Factors Influencing the Purchase Decision of Fitness Customers for Sportswear through Online Channels in Bangkok - Chobngam, Phrit; Iamlaorpakdee, Pranee (Journal of Innovative Business Management Research, 2025)
After the COVID-19 pandemic subsided, health awareness and fitness activities significantly increased. People have become more focused on exercising, both in fitness centers and at home, leading to a growing demand for sportswear and workout equipment. Recognizing this market opportunity, the researcher aimed to study the factors influencing the purchasing decisions of fitness customers when buying sportswear through online channels in Bangkok. This research seeks to understand consumer behavior and needs, ultimately guiding effective marketing strategies. The study aims to examine the marketing factors affecting the purchase decision of fitness customers when buying sportswear online in Bangkok. The key factors analyzed include content marketing, consumer behavior, and perceived quality. This research employs a quantitative approach using survey methods. Data was collected through online questionnaires distributed via Google Forms and QR codes. The sample consisted of 400 fitness customers in Bangkok, and data was analyzed using percentage, mean, standard deviation, and multiple regression analysis. The findings indicate that most respondents are male, single, self-employed, hold a bachelor’s degree, and have an average monthly income between 25,001 - 40,000 THB. The results show that content providing ideas, reasons for purchase, selection criteria, and perceived quality significantly influence the purchasing decisions of fitness customers when buying sportswear online at a 0.05 significance level. However, content that inspires, offers solutions, provides guidance or knowledge, creates emotions/entertainment, identifies the customer, specifies what they buy, and where they buy from does not significantly influence purchasing decisions at the 0.05 significance level.